Clinical Characteristics and Contemporary Prognosis of Ventricular Septal Rupture Complicating Acute Myocardial Infarction: A Single-Center Experience - Wang, Lu; Xiao, Li-Li; Liu, Chao; Zhang, Yan-Zhou; Zhao, Xiao-Yan; Li, Ling; Wang, Xiao-Fang; Dong, Jian-Zeng (Frontiers in Cardiovascular Medicine, 2021)
Objectives: Ventricular septal rupture (VSR) is a rare but lethal complication of acute myocardial infarction (AMI). We conducted a retrospective analysis of the clinical characteristics of VSR patients and explored the risk factors for long-term mortality. Methods: In this single-center cohort study, 127 patients diagnosed with post-AMI VSR between May 2012 and April 2019 were included. Demographic, clinical, operative, and outcome data were collected. The 30-day and long-term mortality were outcomes of interest. Cox proportional hazard regression analysis was used to explore the predictors of long-term mortality. Results: The mean age of the VSR cohort was 66.6 ± 8.7 years, 67 (52.8%) were males. Among the 127 patients,78 patients (61.4%) were medically managed, 31 (24.4%) patients underwent percutaneous transcatheter closure (TCC), and 18 (14.2%) patients received surgical repair. The median follow-up time was 1129 days [interquartile range: 802 - 2019 days]. The 30-day mortality of the medically managed group, percutaneous TCC group, and surgical management group was 93.6%, 22.6%, and 11.1%, respectively; and the long-term mortality was 96.2%, 25.8%, and 22.2%, respectively. VSR repair treatment including surgical management (HR 0.01, 95%CI 0.001 - 0.09, p < 0.001) and percutaneous TCC (HR 0.09, 95%CI 0.03- 0.26, p < 0.001) was associated with a better prognosis, and cardiogenic shock (CS) (HR 9.30, 95%CI 3.38 - 25.62, p < 0.001) was an independent risk factor of long-term mortality. Conclusions: The prognosis of VSR patients without operative management remains poor, especially in those complicated with CS. Timely and improved surgery treatment is needed for better outcomes in VSR patients.